ANALYSIS OF INTERNATIONAL INDEX ON INDONESIAN SHARIA STOCK INDEX - Iman, Shofal; Mawardi, Imron; Sarker, Md Atiqur Rahman (Universitas Airlangga, 2020)
This study aims to determine the influence of long-term and short-term global stock index on the Indonesian Islamic stock index. The approach used is a quantitative approach and uses the Error Correction Model (ECM) method. ECM is an analytical model that can be used in time series data to estimate the effect of independent variables on long-term and short-term use variables. The sample used was taken from secondary data, namely global stock index data consisting of the DJIA, N225 and HSI indices, and the Indonesian sharia stock index in the form of the ISSI index in the period of January 2013 to December 2017, so that 60 samples were obtained. The test results show that in the long run, the DJIA and HSI indices have a significant positive effect on the ISSI index, while the N225 index has a significant negative effect on the ISSI index. In the short term, only the DJIA index has a significant positive effect on the ISSI index.Keywords: Dow Jones Industrial Average, Hang Seng Index, Indonesian Sharia Stock Index, Nikkei 225, Error Correction Model